An Analyzation of Nigerian Democratic Government and Corruption Reflection : Elected Between 2019 and 2024 - Ajiteru,S.A.R; Sulaiman T.H; Abalaka, J.N (Green Social: International Journal of Law and Civil Affairs, 2025)
This paper's goal is to undertake a critical evaluation of Nigerian democracy's speed, practices, patterns, priorities, issues, and future. Although Nigeria is still run by democratically elected officials, after a century as a political entity, Nigeria has yet to institutionalize democracy at the federal and state levels. After more than 50 years of political independence, the study examines some of the challenges Nigeria faces in institutionalizing democracy. These include the nation's colonial past mixed with the whims of deeply ingrained ethnicity; a smug and extravagant leadership; the military's constant meddling in the democratic process; electoral fraud; widespread poverty; and a high rate of illiteracy. According to the publication, corruption is the main cause of most of the aforementioned issues and has essentially taken on a life of its own in Nigeria. However, the study argues that despite the aforementioned, there is still hope for a politically secure and democratically viable People's enthusiasm to vote, the multi-party system's relative stability and sustainability, and the widespread recognition that the only legitimate and well-liked path to gaining political power is through the voting booth are what define the nation. The historical approach of data analysis—simple descriptive collation and analysis of historical data—is used in this paper, which draws its data from primary and secondary source materials.